In situ properties of small and large flux ropes in the solar wind - Janvier, M. (2014)
Two populations of twisted magnetic field tubes, or flux ropes (hereafter, FRs), are detected by in situ measurements in the solar wind. While small FRs are crossed by the observing spacecraft within few hours, with a radius typically less than 0.1 AU, larger FRs, or magnetic clouds (hereafter, MCs), have durations of about half a day. The main aim of this study is to compare the properties of both populations of FRs observed by the Wind spacecraft at 1 AU. To do so, we use standard correlation techniques for the FR parameters, as well as histograms and more refined statistical methods. Although several properties seem at first different for small FRs and MCs, we show that they are actually governed by the same propagation physics. For example, we observe no in situ signatures of expansion for small FRs, contrary to MCs. We demonstrate that this result is in fact expected: small FRs expand similar to MCs, as a consequence of a total pressure balance with the surrounding medium, but the expansion signature is well hidden by velocity fluctuations. Next, we find that the FR radius, velocity, and magnetic field strength are all positively correlated, with correlation factors than can reach a value >0.5. This result indicates a remnant trace of the FR ejection process from the corona. We also find a larger FR radius at the apex than at the legs (up to 3 times larger at the apex), for FR observed at 1 AU. Finally, assuming that the detected FRs have a large-scale configuration in the heliosphere, we derived the mean axis shape from the probability distribution of the axis orientation. We therefore interpret the small FR and MC properties in a common framework of FRs interacting with the solar wind, and we disentangle the physics present behind their common and different features.